KEPEMIMPINAN DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN - IRAWANSYAH, IRAWANSYAH (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2016)
In a leadership, a trust is certainly required to guarantee the  good management.  The management would be better if it is supported by a good leadership. All sides have ties one another, leadership, management, trust, as well as leadership. Those three are influenced by a good education. The purpose of this article is to describe leadership styles viewed from the management of education. Keywords: leadership, education, trust,  management